2015
DOI: 10.1002/cncy.21595
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytic parameters in epidermal growth factor receptor mutation testing for non–small cell lung carcinoma: A review of cytologic series

Abstract: The results from molecular assays can be affected significantly by the preanalytic condition of cytologic samples. The authors review current knowledge on the use of cytologic samples for epidermal growth factor receptor (EGFR) mutation testing in non–small cell lung cancer with a focus on preanalytic parameters. A systematic electronic search of the MEDLINE database was performed to identify original articles that reported the use of cytologic samples for EGFR molecular analysis and included a minimum of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…Thus, we recommended using CB and ICC to evaluate cytological samples derived from FNA. CB also allows for genetic testing and prognostic assessment via PCR, FISH and IHC (22)(23)(24)(25). CB is helpful for diagnosing and subtyping advanced lung cancer, determining precise treatments, and preserving cytological specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we recommended using CB and ICC to evaluate cytological samples derived from FNA. CB also allows for genetic testing and prognostic assessment via PCR, FISH and IHC (22)(23)(24)(25). CB is helpful for diagnosing and subtyping advanced lung cancer, determining precise treatments, and preserving cytological specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Given the diversity of cytopathologic specimen types and the different methods of fixation and processing available, options for procuring DNA from cytologic specimens for molecular analysis vary; material can be successfully obtained from cell blocks, smears, cytospins, and liquid-based preparations. 7,9,11,12,14,[19][20][21][22][23][24][25] Most commonly, cell blocks are used for molecular testing on cytopathologic specimens. 21 The cell block closely approximates surgical pathology material; tissue fragments from cytopathologic specimens are embedded in paraffin and are sectioned akin to surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although liquid-based cytology specimens are not commonly used for molecular testing of lung adenocarcinomas, 21 a few groups have reported their utility. 7,12,14,25 In our laboratory, we have found that the liquid-based cytology specimen is an excellent resource for EGFR mutation analysis and ALK FISH.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cellularity in bronchial wash specimens 24 -and also in bronchial biopsy samples 25,26 -is often relatively low. The worst results with respect to EGFR mutation detection rates have been reported for bronchial washings or brushings and sputum 27 . Bronchial biopsy specimens can also show crush artifact, impairing downstream immunohistochemistry (ihc) or fluorescence in situ hybridization.…”
Section: Respirology Perspectivesmentioning
confidence: 99%
“…Whether cytology or biopsy specimens are obtained, tumour cellularity is the key determinant of the likelihood of successful molecular testing [45][46][47][48] ; both techniques can potentially yield adequate material for diagnostic molecular tests 49 . With respect to cytology specimens, preparation of a cell block is still preferred 24,50 , but other specimens are also suitable for analysis 27 . It is important to recall that molecular testing should still be attempted in specimens in which it is unclear whether the sample will meet all technical requirements.…”
Section: Pathology Perspectivesmentioning
confidence: 99%